Theory of probability and mathematical statistics - Nguyen, Hai Thanh (Khoa Quốc tế, ĐHQGHN, 2020)
The main aim of this module is to provide students with basicstatistical methodsusedin collectingandanalyzingdata, as a basistomake decisionsinbusiness; to help studentslearn tousecomputersoftwaresinprocessing data(eg. Excel), understandandusethe resultsprovided bysoftwares.